Current aspects on vaccines and immunization in the dog and cat. Part I. General aspects-Vaccines and vaccinations in the dog - MYLONAKIS (Μ.Μ. ΜΥΛΩΝΑΚΗΣ), M. M.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; PLEVRAKI (Κ.Γ. ΠΛΕΥΡΑΚΗ), K. G. (Journal of the Hellenic Veterinary Medical Society, 2018)
Immunoprophylaxis plays a pivotal role within the frame of contemporary preventive medicine, enabling the practicing veterinarian to control the most common infectious diseases that may pose a threat on the health status or life itself in the dog and cat. Passive immunization is the administration of preformed antibodies in animals of the same or different species. An alternative to maternal immunity, the natural way of passive immunity, is the use of hyperimmune serum or plasma in colostrum-deprived neonates, in unvaccinated puppies and kittens that belong to high risk groups and in immunocompromised animals. In small animal practice the main vaccine types currently in use for vaccination, an active immunization procedure, include the modified live vaccines, the inactivated and the subunit vaccines. The sound knowledge of these vaccines special features and the potential causes of vaccination failures are essential if a successful vaccination schedule is to be implemented. Vaccinations can start at the 6th week of life in colostrum-afforded neonates while in colostrum-deprived puppies at the 4th week with the use of inactivated vaccines. In the dog, infectious diseases such as distemper, infectious hepatitis, leptospirosis (L. canicola, L. icterohaemorrhagiae), rabies, infectious tracheobronchitis, parvovirus infection, Coronavirus enteritis and babesiosis can be prevented by the use of vaccines which are currently available.